The Clinical Status of Stem Cell Therapy for Ischemic Cardiomyopathy - Xianyun Wang; Jun Zhang; Fan Zhang; Jing Li; Yaqi Li; Zirui Tan; Jie Hu; Yixin Qi; Quanhai Li; Baoyong Yan (Hindawi Limited, 2015)
Ischemic cardiomyopathy (ICM) is becoming a leading cause of morbidity and mortality in the whole world. Stem cell-based therapy is emerging as a promising option for treatment of ICM. Several stem cell types including cardiac-derived stem cells (CSCs), bone marrow-derived stem cells, mesenchymal stem cells (MSCs), skeletal myoblasts (SMs), and CD34+ and CD 133+ stem cells have been applied in clinical researches. The clinical effect produced by stem cell administration in ICM mainly depends on the transdifferentiation and paracrine effect. One important issue is that low survival and residential rate of transferred stem cells in the infracted myocardium blocks the effective advances in cardiac improvement. Many other factors associated with the efficacy of cell replacement therapy for ICM mainly including the route of delivery, the type and number of stem cell infusion, the timing of injection, patient's physical condition, the particular microenvironment onto which the cells are delivered, and clinical condition remain to be addressed. Here we provide an overview of the pros and cons of these transferred cells and discuss the current state of their therapeutic potential. We believe that stem cell translation will be an ideal option for patients following ischemic heart disease in the future.